Idiographic quality of life assessment before radical cystectomy. Issue 2 (30th November 2015) - Anderson, Christopher B.; Rapkin, Bruce; Reaves, Brieyona C.; Sun, Arony J.; Morganstern, Bradley; Dalbagni, Guido; Donat, Machele; Herr, Harry W.; Laudone, Vincent P.; Bochner, Bernard H.
Abstract: Background: We sought to determine if idiographic, or self‐defined, measures added to our understanding of patients with bladder cancer's quality of life (QOL) prior to radical cystectomy (RC). We tested whether idiographic measures increased prediction of global QOL beyond standard (nomothetic) measures of QOL components. Methods: We administered the European Organization for Research and Treatment of Cancer Quality of Life Questionnaires (QLQ)‐C30 and QLQ‐BLM30, and our own idiographic Quality of Life Appraisal Profile prior to RC. Idiographic measures included number of goal statements, distance from goal attainment, and ability to complete goal attainment activities. Multivariate linear regression was used to predict measures of global QOL and related constructs of life satisfaction and mental health. Results: Two hundred fiftheen patients reported a median of 8 (interquartile range [IQR] 6, 11) goals and half had an average goal attainment rating above 6.9 out of 10 (IQR 5.5, 8.2). On multivariable analysis, QLQ‐C30 role functioning and QLQ‐BLM30 future perspective explained 15.7% of the variability in preoperative global QOL. Including goal attainment and activity difficulty explained an additional 12% of global QOL variance. Smaller gains were seen on measures of global health, life satisfaction, mental health, and activity, suggesting that idiographic measures capture aspects of QOL distinct from health and functional status defined by nomothetic scales. Conclusions: Idiographic assessment of QOL added to prediction of global QOL above and beyond health‐related components measured using nomothetic instruments. This self‐defined information may be valuable in communicating with cancer patients about their QOL. Copyright © 2015 John Wiley & Sons, Ltd.